Isolation and identification of microorganisms from cloacal swabs in poultry - Hakkani, Md Golam; Rahman, Md Mostafizer; Akter, Mir Rowshan; Hossain, Md Khaled; Rumi , Nazmi Ara; Rahman , Md Shajedur (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This study was carried out for the isolation and identification of microorganism from cloacal swabs in poultry. During the period from January 2014 to June 2014, the entire research work was conducted in laboratory of the department of Microbiology, Hajee Mohammad Danesh Science and Technology University, Dinajpur. The study was performed with 24 cloacal swabs samples. Samples were collected from the poultry as 6 samples from 5 days of old, 9 samples from 18 days of old and 9 samples from 28 days of old and transferred aseptically to the laboratory. All the experimental work was done under sterile condition. Out of the 24 cloacal swabs samples, 20 isolates were positive. Among 20 positive samples, 6 (30%) E. coli, 5 (25%) Salmonella spp., 4 (20%) Staphylococci spp., 2 (10%) Mycoplasma spp. and 3 (15%) fungus were grown in culture media. In gram's staining from ordinary media (nutrient agar), both gram positive and grams negative bacteria were found. Mycoplasma was positive in Mycoplasma agar (PPLO) where color was changed to slight grayish. On sabourauds dextrose agar medium, the organism were grown as round and raised structure which indicated that fungus was present there. Isolation and identification was done by observing colony morphology, grams staining and standard cultural and biochemical test. Diversified bacterial species were prevalent in cloacal swabs of broiler. However E. coli, Salmonella spp. infection might make the birds vulnerable for easy access of infection. It could be concluded that the organisms may pass through the faeces to the environment and cause a potential human health hazards and can cause illness. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 441-447